THE STRATEGY TO INCREASE THE COVERAGE OF HIV TESTING AMONG ADOLESCENT: A SYSTEMATICAL LITERATURE REVIEW TO SEEK EFFECTIVE INTERVENTION: Seeking Effective Intervention - Yunita Amraeni (STIKes Mandala Waluya Kendari, 2022)
Background: HIV testing programs have not been able to reach all populations at risk of HIV transmission. Lodging in adolescents vulnerable to HIV, program coverage is low. The purpose of this article is to identify various models of effective interventions that can improve the coverage of HIV testing among adolescents. Methods: This study is a systematic literature review with a time frame from 2011 to the present, with a geographical reach across the country. Rate the quality of the research methodology conducted by several components of the assessment indicators. Results: By keyword intervention strategies, increase coverage of HIV testing and adolescents 2343 articles obtained from a number of online journals database. Screening with inclusion criteria yielded 94 articles, and by exclusion criteria obtained 13 articles. Generally, coverage of HIV testing interventions in adolescents at increased each strategy. Community-based strategies appear to be more effective based on WHO standards, with coverage achieved around 80%, compared to health facility-based strategies with an average coverage of around 50%. HIV positive number reached 16% of health facilities. While the value of the highest achievements in community based around 12%. Conclussions:Community-based intervention is better to reach teens, but the community component must collaborate well with the ease of access to health facilities for HIV testing services. Development interventions in adolescents need to be equipped with a research method that can provide a strong evidens about the effectiveness of coverage of HIV testing among adolescents. Such research is not yet performed in Indonesia.